2004
DOI: 10.1111/j.1745-4557.2004.tb00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbiological, Physicochemical and Sensory Qualities of Chitosan Tofu During Storage

Abstract: Tofu containing both low and high viscosity chitosan was prepared and changes in the microbiological, physicochemical and sensory properties of the tofu during storage were investigated. The colony forming units of mesophilic and psychrotrophic microorganisms in tofu containing high viscosity chitosan were markedly lower during storage than those in the control tofu as well as the tofu containing low viscosity chitosan. The pH of the tofu samples increased during storage. The L and a values of the tofu, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…2010). Kim and Son (2004) reported that tofu containing chitosan scored higher than the other control tofu samples. In addition, chitosan‐coated samples (salted and dried horse mackerel) received higher overall consumer acceptance compared with the control group (Ahn and Lee 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2010). Kim and Son (2004) reported that tofu containing chitosan scored higher than the other control tofu samples. In addition, chitosan‐coated samples (salted and dried horse mackerel) received higher overall consumer acceptance compared with the control group (Ahn and Lee 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it was indicated that chitosans improved the quality characteristics of rainbow and carp fillet samples, and extended the shelf life during the cold and frozen storage, which was supported by the results of microbiological and sensory evaluation analyses (Fan et al 2009;Ojagh et al 2010). Kim and Son (2004) reported that tofu containing chitosan scored higher than the other control tofu samples. In addition, chitosancoated samples (salted and dried horse mackerel) received higher overall consumer acceptance compared with the control group (Ahn and Lee 1992).…”
Section: Sensory Evaluationmentioning
confidence: 97%
“…An increase in pH was observed, however, for tofu packaged in air and in 100% N 2 , at the end of the storage period. This can be attributed to microbial production of peptides, amino acids or amines (Kim et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that tofu is susceptible to microbial spoilage because of its high nutrient and moisture content (>75%) and its relatively neutral pH (5·8–6·2) (Champagne et al. 1991; Kim et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation